Rates and predictors of co-occurring autism spectrum disorder in boys with fragile X syndrome. (February 2020) - Haebig, Eileen; Sterling, Audra; Barton-Hulsey, Andrea; Friedman, Laura
Background and aims: Males with fragile X syndrome display many behavioral features of autism spectrum disorder. Despite this overlap, our understanding of autism spectrum disorder symptoms and severity in fragile X syndrome is limited due to variation in assessment methods in the literature. Furthermore, the relationship between autism spectrum disorder symptoms and child characteristics, like age, language, and cognitive abilities, are not well understood in individuals with fragile X syndrome. Therefore, the first research aim was to compare the rates of autism spectrum disorder classifications from three commonly reported autism spectrum disorder assessments in the literature. Our second research aim was to examine the relationship between autism spectrum disorder characteristics and other child characteristics. Methods: The present study compared autism spectrum disorder classifications and symptoms using the Autism Diagnostic Observation Schedule, Autism Diagnostic Interview, Revised, and Childhood Autism Rating Scale, second edition in a sample of 33 school-age and adolescent boys with fragile X syndrome. In addition, the participants completed nonverbal IQ testing, expressive vocabulary and grammar tests, and a conversation language sample. Results: The majority of the participants met criteria for autism spectrum disorder on the Autism Diagnostic Observation Schedule (96.97%) and Autism Diagnostic Interview, Revised (90.91%), while only half met criteria for autism spectrum disorder on the Childhood Autism Rating Scale, second edition. Sixteen boys (48.48%) met criteria for autism spectrum disorder on all three measures, and all participants met criteria for autism spectrum disorder on at least one measure. Expressive vocabulary accounted for a unique amount of variance in Childhood Autism Rating Scale, second edition and Autism Diagnostic Observation Schedule scores. Additionally, grammatical complexity accounted for a unique amount of variance in Childhood Autism Rating Scale, second edition scores. None of the child variables accounted for the variance found in Autism Diagnostic Interview, Revised scores. Although nonverbal IQ scores did not account for a significant amount of variance on the Autism Diagnostic Observation Schedule, Autism Diagnostic Interview, Revised, and Childhood Autism Rating Scale, Second Edition, boys who met criteria for autism spectrum disorder on all three measures had lower nonverbal IQ compared to the boys who did not. Additionally, mean length of utterance and expressive vocabulary scores were lower in the boys who met criteria for autism spectrum disorder on all three measures than those who did not. Conclusions: Our findings identify areas of overlap and difference in the Autism Diagnostic Observation Schedule, Autism Diagnostic Interview, Revised, and Childhood Autism Rating Scale, second edition when used with males with fragile X syndrome. Variation in assessments may differentially identify the phenotypic behaviors of boys with fragile X syndrome that lead to a co-diagnosis of autism spectrum disorder, which contributes to the variation in reported co-morbidity of fragile X syndrome and autism spectrum disorder. Also, expressive language abilities, especially expressive vocabulary, are associated with autism spectrum disorder symptomatology. Implications: When interpreting comorbid fragile X syndrome and autism spectrum disorder rates in the literature, it is important to consider the assessment tool that was used. Although the assessments that we used in the present study yielded scores that were highly correlated (i.e. Autism Diagnostic Observation Schedule and Childhood Autism Rating Scale, second edition), their categorical classifications did not align perfectly. Our findings also highlight the importance of considering language skills when assessing autism spectrum disorder severity in fragile X syndrome.